A rare earth modified plastic and preparation method thereof
By using lanthanum humate modified polypropylene film in lithium battery separator, the low wettability and thermal stability of polypropylene separator are solved, high ionic conductivity and excellent electrochemical performance are achieved, and lithium batteries are improved Safety and temperature range.
Patent Information
- Application Number
- CN202411427227.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The low wettability and thermal stability of polypropylene lithium battery separators make it difficult for the electrolyte to penetrate and retain effectively, affecting ionic conductivity and electrochemical performance, and thermal shrinkage and deformation may cause battery short circuit and explosion.
Using lanthanum humate as an additive mixed with polypropylene and copolymer elastomer, polypropylene film is prepared by dry method, which improves its softening failure temperature and mechanical strength, enhances thermal stability and liquid absorption, and forms high ionic conductivity and excellent electrical Chemical properties of lithium battery separators.
The high ionic conductivity and excellent and stable electrochemical performance of the lithium battery separator in thinner conditions are achieved, which improves the safety and temperature range of the lithium battery, while maintaining mechanical strength and good electrolyte wetting.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polypropylene plastics, and specifically relates to a rare earth modified plastic and a preparation method thereof. The rare earth modified plastic is a polypropylene plastic modified and compounded with lanthanum humate. The rare earth modified plastic has good thermal stability and mechanical strength, can be used for lithium battery diaphragms, and has good wettability to electrolytes. Background Art
[0002] As one of the most important components of lithium-ion batteries, the diaphragm is placed between the positive and negative electrodes and does not directly participate in the electrochemical reaction, but its structure and performance play an important role in the battery performance. The main function of the diaphragm is to prevent physical contact between the electrodes. At the same time, the pore structure of the diaphragm is the transmission channel for lithium ions between the positive and negative electrodes, so that the electrochemical reaction of the lithium-ion battery can proceed. It can be seen that the performance of the diaphragm directly affects the electrochemical performance of the lithium-ion battery. A lithium battery separator with excellent performance must have at least the following characteristics and requirements while meeting the requirements of strong electronic insulation, high ionic conductivity and cost factors: (1) Chemical stability: In order to obtain long-life battery performance, the separator must resist its own degradation and reduction in mechanical strength during the charge and discharge process; and have the ability to stabilize the electrolyte and electrode materials; (2) Electrolyte wettability: The effective wetting of the electrolyte on the separator determines the impedance of ions during transmission. The better the wettability, the smaller the impedance of lithium ion migration inside the battery, and thus the better the electrochemical performance of the battery. The complete wetting of the separator by the electrolyte is also beneficial to the overall assembly of the battery; (3) Thickness: The thickness of the separator plays a key role in safety and electrochemical performance. The separator should have the best mechanical strength while having the minimum thickness, so that it can resist the growth and penetration of lithium dendrites and withstand a certain amount of pressure during the assembly process. At the same time, it should also provide high ionic conductivity to achieve ideal electrochemical performance. (4) Thermal shrinkage rate: When the lithium battery is working, the internal electrochemical reaction process will generate heat. If the melting point of the separator is too low, this part of the heat will cause the separator to shrink, which may lead to direct contact between the positive and negative electrodes, causing a short circuit in the battery. In severe cases, it may cause an explosion, posing a serious safety hazard.
[0003] At present, commercial diaphragms are basically based on polyethylene and polyolefins. Among them, polypropylene film has a higher melting point, which will greatly improve the safety performance of the battery. Therefore, it is widely used in lithium battery diaphragm base film. Polypropylene diaphragms have good mechanical strength and electrochemical stability, but their inherent low polarity and surface energy lead to poor wettability of the diaphragm, making it difficult for the electrolyte to effectively penetrate and retain on the surface of the diaphragm, which in turn leads to the formation of electrolyte dead zones inside the battery, increasing the overall impedance of the battery, thereby reducing the ionic conductivity and affecting its electrochemical properties. At the same time, poor thermal stability can easily cause thermal shrinkage deformation of the diaphragm, and may even cause battery explosion. Therefore, it is very important to improve the wettability and thermal stability of polypropylene diaphragms. In order to improve the absorption and retention of the electrolyte, the current method is mainly to increase the affinity between the diaphragm and the electrolyte, thereby slowing down the decomposition and loss of the electrolyte and ensuring good contact between the diaphragm and the electrolyte. In addition, sufficient electrolyte also enables the diaphragm to have a fast ion transmission channel at high current density, so that the battery has excellent electrochemical performance at high current density. At the same time, good wettability also reduces the time cost of battery assembly. Grafting and coating are common practices to improve the wettability of polypropylene diaphragms. For example, CN104403195A discloses the raw materials and diaphragm processing methods of highly wettable lithium-ion battery diaphragms, and the raw materials are made of polyolefin resin and maleic anhydride grafted polypropylene. The diaphragm preparation method includes the following steps: Step 1: The polyolefin resin, maleic anhydride grafted polypropylene and other additives are stirred evenly by a stirring mixer to obtain a mixture I; Step 2: Add the mixture I to the extrusion casting system for casting to prepare a precursor film; Step 3: Place the obtained precursor film in a constant temperature oven for annealing; Step 4: The annealed precursor film is longitudinally stretched to prepare a diaphragm with a microporous structure, and the prepared diaphragm has high wettability and low cost. CN110137416A discloses a method for preparing a polyolefin lithium battery diaphragm, which uses a porous polyolefin diaphragm as a substrate, and one or both sides of the polyolefin diaphragm are coated with a modified polymethyl methacrylate (PMMA) organic coating, wherein the modified polymethyl methacrylate organic matter is an organic matter composited from inorganic oxide nanoparticles and polymethyl methacrylate. The diaphragm has good electrolyte wettability and can prevent the swelling of high molecular polymers from causing blockage of ion channels. CN111725468B discloses a silicon dioxide inorganic nanoparticle reinforced polyolefin diaphragm, which utilizes the excellent thermal stability of silicon dioxide inorganic nanoparticles and is coated on the polyolefin diaphragm through a binder to improve the thermal stability of the diaphragm, and the composite diaphragm has good electrolyte wettability. However, the porosity of the general coating is not high enough, which greatly reduces the liquid absorption rate of the diaphragm, affects the migration of lithium ions, and increases the internal resistance of the battery. At the same time, the coating applied later is also easy to fall off, thus limiting the performance and stability of the lithium-ion battery.
[0004] In view of the poor thermal stability of polypropylene, the conventional practice is to perform surface modification. The melting point of polypropylene is 165°C. The heat generated during the electrochemical reaction causes the diaphragm to shrink, which in turn causes a short circuit between the positive and negative electrodes due to direct contact, which has a serious impact on the safety performance of the battery. CN118507978A discloses a diaphragm, including: attapulgite, polyacrylonitrile oxide and polyvinyl alcohol. On the premise of ensuring that the diaphragm has good electrolyte adsorption performance, effective diffusion pathways, small interface impedance, good thermal insulation performance, heat resistance and flame retardant performance, the thermal stability and ion conductivity of the diaphragm are further improved. CN103992505A discloses a method for improving the hydrophilicity and thermal stability of a polypropylene lithium ion battery diaphragm. Anionic and cationic polyelectrolytes containing anionic and cationic structural units are prepared respectively by aqueous solution polymerization. The pretreated polypropylene diaphragm is repeatedly and alternately immersed in two polyelectrolyte solutions, so that the polymer polyelectrolyte self-assembles to the surface of the polypropylene diaphragm under the action of electrostatic force, thereby improving the hydrophilicity and thermal stability of the diaphragm. CN109148795A discloses a method for preparing a battery composite diaphragm, combining an organic material polypropylene film and an inorganic ceramic material to prepare a composite diaphragm, wherein the inorganic ceramic material is distributed in the three-dimensional structure of the composite diaphragm to form a specific rigid skeleton, and the extremely high thermal stability can effectively prevent the diaphragm from shrinking and melting under thermal runaway conditions, thereby improving the safety of the battery. CN114497894A discloses a Janus diaphragm with single-sided conductivity for lithium batteries, wherein the Janus diaphragm is prepared by coating, scraping, and phase conversion of polyaryletherketone containing carbon nanotubes on the surface of a high-concentration ozone-modified polypropylene film, and has excellent thermal stability and electrochemical properties. However, the above-mentioned practices such as surface coating modification or composite layer diaphragms will inevitably increase the thickness of the diaphragm, which is not conducive to improving the energy density of lithium-ion batteries. Therefore, it is necessary to provide a polypropylene diaphragm with excellent thermal stability and electrolyte infiltration without increasing the thickness of the diaphragm, so that it has higher ionic conductivity and excellent and stable electrochemical properties and mechanical strength, and meets the higher use requirements of lithium batteries. Summary of the invention
[0005] In order to solve the defects in the prior art, the present invention provides a rare earth modified plastic and a preparation method thereof, wherein lanthanum humate is used as an additive for the preparation of a polypropylene film, and a polypropylene film is prepared by a dry method by mixing lanthanum humate with polypropylene and a copolymer elastomer raw material. Compared with a pure polypropylene film, the film has a higher softening failure temperature, and the film has good mechanical strength, thermal stability and excellent liquid absorption. When the film is used for a lithium battery separator, the separator can have high ionic conductivity and excellent and stable electrochemical properties as well as mechanical strength when the separator is thin, thereby meeting the requirements for the use of lithium batteries.
[0006] In order to achieve the above-mentioned invention purpose, the present application provides a rare earth modified plastic, wherein the plastic is a polypropylene film, the film thickness is 5~20μm, lanthanum humate is used as an additive in the modified plastic, and the film breaking temperature of the modified polypropylene film is ≥180℃.
[0007] Usually the melting point of polypropylene is 165°C. When the internal temperature of a lithium battery exceeds 165°C due to thermal runaway, the diaphragm melts, the positive and negative electrodes short-circuit, and the lithium battery is scrapped. During the preparation and use of polypropylene film, the lanthanum ions in lanthanum humate react with unstable groups in the polypropylene molecules to inhibit the degradation of polypropylene. In addition, they can capture free radicals and prevent chain reactions, thereby effectively inhibiting the thermal degradation of polypropylene and improving its thermal stability. The film prepared using lanthanum humate as an additive in the present application can increase the melting temperature of the film, avoid the rapid heating of some areas during the internal charging and discharging process of the lithium battery using the diaphragm, and avoid melting failure caused by the instantaneous temperature exceeding 165°C, which protects the lithium battery to a certain extent and increases its operating temperature range.
[0008] Furthermore, in terms of mass percentage, the raw materials of the rare earth modified plastic include 75% to 95% polypropylene as main material, 2% to 10% copolymer elastomer and 1% to 15% lanthanum humate. Further preferably, the rare earth modified plastic is prepared from 80% to 90% polypropylene as main material, 5% to 10% copolymer elastomer and 5% to 10% lanthanum humate as raw materials.
[0009] Furthermore, the copolymer elastomer includes polyethylene butene copolymer elastomer and / or polyethylene propylene copolymer elastomer.
[0010] Using polyethylene butene copolymer elastomer and / or polyethylene propylene copolymer elastomer as raw materials, the polyethylene in the prepared plastic film is uniformly dispersed in the film. The melting point of polyethylene is 130~135℃, which is lower than 165℃ of PP. When the overall temperature of the lithium battery exceeds the melting point of polyethylene, the polyethylene inside the film melts and seals the pores in the PP film, preventing the transmission of lithium. The internal disconnection reaction proceeds, which can enhance the safety of the lithium battery to a certain extent.
[0011] Furthermore, the preparation method of lanthanum humate is as follows: (1) preparing a humic acid aqueous solution: weighing 0.5 kg of humic acid powder and adding it to 100 L of deionized water containing 0.4 kg of NaOH, stirring continuously for 10 to 30 min until the solution is evenly dispersed, adjusting the pH of the solution to 7 to 8 under stirring conditions, and filtering to obtain a humic acid solution;
[0012] (2) Weigh 1-10 mol of lanthanum nitrate and dissolve it in 50 L of deionized water. Add the lanthanum nitrate solution dropwise to the humic acid solution obtained in step (1) under stirring. After dispersion for 10 min, transfer the mixed solution into a high-pressure reactor and react at 100-150° C. for 6-10 h. Rinse and dry to obtain the product.
[0013] Humic acid is a natural surfactant, mainly composed of carbon, hydrogen, oxygen, nitrogen and other elements. Its structure is mainly linked to each other by bridge bonds. The functional groups are mainly distributed on aromatic rings, various heterocyclic rings and side chains. It contains hydrophobic parts composed of organic hydrocarbons and carbon chains, as well as active ionic groups such as carboxyl groups and hydrophilic parts composed of non-ionic polar groups such as phenols, alcohols and amides. The surface of humic acid is porous, similar to a sponge-like structure, with a large specific surface area, viscosity, dispersibility and strong adsorption capacity. It can be used as a complexing agent to react with rare earth lanthanum ions to form a stable complex product. There are both hydrophobic groups and hydrophilic groups in humic acid, so that lanthanum humate can be effectively dispersed with the main component of polypropylene and copolymer elastomer during high-temperature mixing when used as an additive to prepare polypropylene film, improve the dispersion efficiency and improve the mechanical stability of the film, prevent the swelling of the diaphragm during the electrochemical process, reduce the shrinkage and breakage of the film during use, maintain the pore structure of the diaphragm, and facilitate the penetration of the electrolyte. When the polypropylene plastic is used for lithium battery separators, the various functional groups and groups in humic acid can interact with the ions in the electrolyte, making it easier for the electrolyte to penetrate into the separator and promoting the infiltration of the electrolyte into the separator. At the same time, the presence of lanthanum humate can also improve the surface properties of the separator, reduce its surface tension, and make it easier for the electrolyte to spread on the surface of the separator, thereby improving the infiltration speed and efficiency.
[0014] Another object of the present application is to provide a method for preparing rare earth modified plastics, comprising the following steps: weighing a polypropylene main material, a copolymer elastomer and lanthanum humate in proportion, adding the above components into a high-speed mixer and mixing them evenly; subjecting the mixed raw materials to melt extrusion, sheet casting, biaxial stretching treatment and heat treatment in sequence to obtain a polypropylene film intermediate; and subjecting the polypropylene film intermediate to corona treatment to obtain a polypropylene film.
[0015] Furthermore, the copolymer elastomer includes polyethylene butene copolymer elastomer and / or polyethylene propylene copolymer elastomer.
[0016] Furthermore, the preparation method of lanthanum humate is as follows: (1) preparing a humic acid aqueous solution: weighing 0.5 kg of humic acid powder and adding it to 100 L of deionized water containing 0.4 kg of NaOH, stirring continuously for 10 to 30 min until the solution is evenly dispersed, adjusting the pH of the solution to 7 to 8 under stirring conditions, and filtering to obtain a humic acid solution;
[0017] (2) Weigh 1-10 mol of lanthanum nitrate and dissolve it in 50 L of deionized water. Add the lanthanum nitrate solution dropwise to the humic acid solution obtained in step (1) under stirring. After dispersion for 10 min, transfer the mixed solution into a high-pressure reactor and react at 100-150° C. for 6-10 h. Rinse and dry to obtain the product.
[0018] Furthermore, the rotation speed of the high-speed stirrer is 1000-1500 r / min.
[0019] Furthermore, the biaxial stretching treatment includes a longitudinal stretching treatment and a transverse stretching treatment performed sequentially, and the process conditions of the longitudinal stretching treatment include: a stretching temperature of 130°C~160°C, and a longitudinal stretching ratio of 7:1~10:1; the process conditions of the transverse stretching treatment include: a stretching temperature of 150°C~170°C, and a stretching ratio of 3:1~6:1.
[0020] Furthermore, the heat treatment temperature is 120° C. to 130° C., the heat treatment time is 10 to 60 s, the corona treatment power is 80 kW, and the line speed is 80 to 200 m / min.
[0021] Furthermore, the polypropylene film obtained by the method has a thickness of 5-20 μm and a film breaking temperature of ≥180°C.
[0022] The present application also provides an application of a rare earth modified plastic in a lithium battery. The plastic is a polypropylene film, which can be used as a lithium ion battery separator and has good mechanical strength, thermal stability and electrolyte wettability.
[0023] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0024] 1. The present invention proposes for the first time to use lanthanum humate as a raw material for plastic modification. The polypropylene film prepared using lanthanum humate as a raw material has a stable temperature of not less than 180°C, good thermal stability, high mechanical strength, good wettability to electrolyte when used as a lithium battery separator, and high ion conductivity;
[0025] 2. The raw materials of this application are simple, the preparation method is simple and operable, and the valuable utilization of humic acid can be achieved, with good market prospects and economic benefits. DETAILED DESCRIPTION
[0026] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0027] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0028] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0029] Example 1
[0030] A lanthanum modified polypropylene film comprises, by weight percentage, 75% of polypropylene masterbatch, 10% of polyethylene butene copolymer elastomer and 15% of lanthanum humate.
[0031] The method for preparing a lanthanum-modified polypropylene film comprises the following steps: (1) preparing lanthanum humate: weighing 500 g of humic acid powder and adding it to 100 L of deionized water containing 400 g of NaOH, stirring continuously for 10 min until the solution is evenly dispersed, adjusting the pH value of the solution to 7 under stirring conditions, and filtering to obtain a humic acid solution; weighing 1 mol of lanthanum nitrate and dissolving it in 50 L of deionized water, adding the lanthanum nitrate solution dropwise to the humic acid solution under stirring conditions, dispersing for 10 min, transferring the mixed solution into a high-pressure reactor, reacting at 100° C. for 6 h, rinsing, and drying; (2) weighing a polypropylene masterbatch, a polyethylene butene copolymer elastomer, and the prepared lanthanum humate according to proportion, and adding them to a high-pressure reactor; The mixture was mixed evenly in a mixer at a speed of 1000 r / min; (3) the mixed raw materials were sequentially subjected to melt extrusion, casting, biaxial stretching and heat treatment to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment includes a longitudinal stretching treatment at a stretching ratio of 7:1 at 130°C and a transverse stretching treatment at a stretching ratio of 3:1 at 150°C, and the heat treatment is heat preservation at 120°C for 10s; (4) the polypropylene film intermediate was subjected to corona treatment, with a corona power of 80kW and a line speed of 80m / min to obtain a polypropylene film. The film prepared by measurement has a thickness of 20μm, a longitudinal tensile strength of 190MPa, a porosity of 46.8%, a heat shrinkage rate of 0.57% at 160°C, and a film breaking temperature of 193°C, which meets the requirements of GB / T36363-2018 polyolefin separator for lithium ion batteries. When the film is used for lithium ion battery separators, the battery first efficiency is 94% and the capacity retention rate is 89% according to GB / T43695-2024 standard. A mixed solvent electrolyte of ethylene carbonate (EC), dimethyl carbonate (EMC) and ethyl methyl carbonate (EC) with a volume ratio of 1:1:1 of 1 M LiPF6 was selected to carry out a static contact angle test on the obtained membrane. The measured contact angle of the membrane electrolyte was 13.4°.
[0032] Example 2
[0033] A lanthanum modified polypropylene film comprises, by weight percentage, 95% of polypropylene masterbatch, 4% of polyethylene-propylene copolymer elastomer and 1% of lanthanum humate.
[0034] The method for preparing a lanthanum-modified polypropylene film comprises the following steps: (1) preparing lanthanum humate: weighing 500 g of humic acid powder and adding it to 100 L of deionized water containing 400 g of NaOH, stirring continuously for 30 min until the solution is evenly dispersed, adjusting the pH value of the solution to 8 under stirring conditions, and filtering to obtain a humic acid solution; weighing 10 mol of lanthanum nitrate and dissolving it in 50 L of deionized water, adding the lanthanum nitrate solution dropwise to the humic acid solution under stirring conditions, dispersing for 10 min, transferring the mixed solution into a high-pressure reactor, reacting at 150° C. for 10 h, rinsing, and drying; (2) weighing a polypropylene masterbatch, a polyethylene butene copolymer elastomer, and the prepared lanthanum humate according to proportion, and adding them to a high-pressure reactor; The mixture was mixed evenly in a mixer at a speed of 1500r / min; (3) the mixed raw materials were sequentially subjected to melt extrusion, casting, biaxial stretching and heat treatment to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment includes a longitudinal stretching treatment at a stretching ratio of 10:1 at 160°C and a transverse stretching treatment at a stretching ratio of 6:1 at 170°C, and the heat treatment is heat preservation at 130°C for 60s; (4) the polypropylene film intermediate was subjected to corona treatment at a corona power of 80kW and a line speed of 200m / min to obtain a polypropylene film. The film prepared by measurement has a thickness of 5.1μm, a longitudinal tensile strength of 165MPa, a porosity of 35.4%, a heat shrinkage rate of 0.85% at 160°C, and a film breaking temperature of 180°C, which meets the requirements of GB / T36363-2018 polyolefin separators for lithium-ion batteries. When the film is used as a lithium-ion battery separator, the battery first efficiency is 91% and the capacity retention rate is 87% according to the GB / T43695-2024 standard. A mixed solvent electrolyte of ethylene carbonate (EC), dimethyl carbonate (EMC) and ethyl methyl carbonate (EC) with a volume ratio of 1:1:1 in 1 M LiPF6 is selected to test the static contact angle of the obtained separator. The contact angle of the separator electrolyte is measured to be 15.7°.
[0035] Example 3
[0036] A lanthanum modified polypropylene film comprises, by weight percentage, 80% of polypropylene masterbatch, 10% of polyethylene propylene copolymer elastomer and 10% of lanthanum humate.
[0037] The method for preparing a lanthanum-modified polypropylene film comprises the following steps: (1) preparing lanthanum humate: weighing 500 g of humic acid powder and adding it to 100 L of deionized water containing 400 g of NaOH, stirring continuously for 30 min until the solution is evenly dispersed, adjusting the pH value of the solution to 7 under stirring conditions, and filtering to obtain a humic acid solution; weighing 8 mol of lanthanum nitrate and dissolving it in 50 L of deionized water, adding the lanthanum nitrate solution dropwise to the humic acid solution under stirring conditions, dispersing for 10 min, transferring the mixed solution into a high-pressure reactor, reacting at 130° C. for 10 h, rinsing, and drying; (2) weighing a polypropylene masterbatch, a polyethylene butene copolymer elastomer, and the prepared lanthanum humate according to proportion, and adding them to a high-pressure reactor; The mixture was mixed evenly in a mixer at a speed of 1200r / min; (3) the mixed raw materials were sequentially subjected to melt extrusion, casting, biaxial stretching and heat treatment to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment includes a longitudinal stretching treatment at a stretching ratio of 8:1 at 140°C and a transverse stretching treatment at a stretching ratio of 5:1 at 160°C, and the heat treatment is heat preservation at 120°C for 30s; (4) the polypropylene film intermediate was subjected to corona treatment at a corona power of 80kW and a line speed of 100m / min to obtain a polypropylene film. The film thickness prepared by measurement was 10.3μm, the longitudinal tensile strength was 182MPa, the porosity was 43.1%, the thermal shrinkage at 160°C was 0.65%, and the film breaking temperature was 187°C, which met the requirements of GB / T36363-2018 polyolefin separator for lithium ion batteries. When this film is used as a lithium-ion battery separator, the battery initial efficiency is measured according to the GB / T43695-2024 standard and the capacity retention rate is 93%.
[0038] Example 4
[0039] A lanthanum modified polypropylene film comprises, by weight percentage, 85% of polypropylene masterbatch, 7% of a mixture of polyethylene butene copolymer elastomer and polyethylene propylene copolymer elastomer in a weight ratio of 1:1, and 8% of lanthanum humate.
[0040] The method for preparing a lanthanum-modified polypropylene film comprises the following steps: (1) preparing lanthanum humate: weighing 500 g of humic acid powder and adding it to 100 L of deionized water containing 400 g of NaOH, stirring continuously for 30 min until the solution is evenly dispersed, adjusting the pH value of the solution to 7 under stirring conditions, and filtering to obtain a humic acid solution; weighing 5 mol of lanthanum nitrate and dissolving it in 50 L of deionized water, adding the lanthanum nitrate solution dropwise to the humic acid solution under stirring conditions, dispersing for 10 min, transferring the mixed solution into a high-pressure reactor, reacting at 110° C. for 7 h, rinsing, and drying; (2) weighing a polypropylene masterbatch, a polyethylene butene copolymer elastomer, and the prepared lanthanum humate according to proportion, and adding them to a high-speed stirring reactor; The mixture was mixed evenly in a mixer at a speed of 1200r / min; (3) the mixed raw materials were sequentially subjected to melt extrusion, casting, biaxial stretching and heat treatment to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment includes a longitudinal stretching treatment at a stretching ratio of 7:1 at 130°C and a transverse stretching treatment at a stretching ratio of 4:1 at 160°C, and the heat treatment is heat preservation at 120°C for 20s; (4) the polypropylene film intermediate was subjected to corona treatment at a corona power of 80kW and a line speed of 120m / min to obtain a polypropylene film. The film thickness prepared by measurement was 18.5μm, the longitudinal tensile strength was 177MPa, the porosity was 42.8%, the thermal shrinkage at 160°C was 0.72%, and the film breaking temperature was 181°C, which met the requirements of GB / T36363-2018 polyolefin separator for lithium ion batteries.
[0041] Comparative Example 1
[0042] A lanthanum modified polypropylene film comprises, by weight percentage, 85% of polypropylene masterbatch, 7% of a mixture of a polyethylene butene copolymer elastomer and a polyethylene propylene copolymer elastomer in a weight ratio of 1:1, and 8% of lanthanum oxide.
[0043] The preparation method of the lanthanum modified polypropylene film comprises the following steps: (1) weighing polypropylene masterbatch, polyethylene butene copolymer elastomer and lanthanum oxide particles in proportion, adding them into a high-speed mixer and mixing them evenly, with a rotation speed of 1200r / min; (2) sequentially performing melt extrusion, sheet casting, biaxial stretching treatment and heat treatment on the mixed raw materials to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment comprises sequentially performing longitudinal stretching treatment at a stretching ratio of 7:1 at 130°C and transverse stretching treatment at a stretching ratio of 4:1 at 160°C, and the heat treatment is heat preservation at 120°C for 20s; (3) performing corona treatment on the polypropylene film intermediate, with a corona power of 80kW and a line speed of 120m / min, to obtain a polypropylene film. The prepared film has a thickness of 17.1μm, a longitudinal tensile strength of 131MPa, a porosity of 32.6%, a heat shrinkage rate of 0.42% at 160°C, and a film breaking temperature of 173°C, but a small amount of undispersed particles can be seen on the surface of the film. A mixed solvent electrolyte of ethylene carbonate (EC), dimethyl carbonate (EMC) and ethyl methyl carbonate (EC) with a volume ratio of 1:1:1 of 1 M LiPF6 was selected to carry out a static contact angle test on the obtained membrane. The measured contact angle of the membrane electrolyte was 47.6°.
[0044] Comparative Example 2
[0045] A lanthanum modified polypropylene film comprises, by weight percentage, 85% of polypropylene masterbatch, 7% of a mixture of polyethylene butene copolymer elastomer and polyethylene propylene copolymer elastomer in a weight ratio of 1:1, and 8% of humic acid.
[0046] The method for preparing a lanthanum-modified polypropylene film comprises the following steps: (1) weighing a polypropylene masterbatch, a polyethylene butene copolymer elastomer and a humic acid in proportion, adding the masterbatch into a high-speed mixer and mixing them evenly at a rotation speed of 1200 r / min; (2) subjecting the mixed raw materials to melt extrusion, sheet casting, biaxial stretching treatment and heat treatment in sequence to obtain a polypropylene film intermediate, wherein the biaxial stretching treatment comprises a longitudinal stretching treatment at a stretching ratio of 7:1 at 130° C. and a transverse stretching treatment at a stretching ratio of 4:1 at 160° C. in sequence, and the heat treatment is heat preservation at 120° C. for 20 seconds; and (3) subjecting the polypropylene film intermediate to a corona treatment at a corona power of 80 kW and a line speed of 120 m / min to obtain a polypropylene film. The film thickness was measured to be 16.8μm, the longitudinal tensile strength was 113MPa, the porosity was 40.5%, the thermal shrinkage at 160℃ was 2.46%, and the film breaking temperature was 167℃. When the film was used for lithium-ion battery separators, the battery first efficiency was 73% and the capacity retention rate was 81% according to the GB / T43695-2024 standard. A mixed solvent electrolyte of ethylene carbonate (EC), dimethyl carbonate (EMC) and ethyl methyl carbonate (EC) with a volume ratio of 1:1:1 was selected to test the static contact angle of the obtained separator. The contact angle of the separator electrolyte was measured to be 23.1°.
[0047] From the test results of the above embodiments and comparative examples, it can be seen that the polypropylene film prepared in the present application has good mechanical properties, high thermal stability, and the film rupture temperature is increased to above 180°C. Through the test on lithium-ion batteries, it can be seen that the lithium battery using the diaphragm has a high first efficiency and a high capacity retention rate. It can be seen that the diaphragm has high ion conductivity and good electrolyte wettability.
[0048] The above is a detailed introduction to a rare earth modified plastic and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A rare earth modified plastic, the plastic is a polypropylene film, the film thickness is 5-20 μm, characterized in that: The modified plastic uses lanthanum humate as an additive, and the film breaking temperature of the modified polypropylene film is ≥180°C; In terms of mass percentage, the raw materials of the rare earth modified plastic include 75% to 95% polypropylene main material, 2% to 10% copolymer elastomer and 1% to 15% lanthanum humate; The copolymer elastomer includes polyethylene butene copolymer elastomer and / or polyethylene propylene copolymer elastomer; The preparation method of lanthanum humate is as follows: (1) preparing a humic acid aqueous solution: weighing 0.5 kg of humic acid powder and adding it to 100 L of deionized water containing 0.4 kg of NaOH, stirring continuously for 10 to 30 minutes until the solution is evenly dispersed, adjusting the pH of the solution to 7 to 8 under stirring conditions, and filtering to obtain a humic acid solution; (2) Weigh 1-10 mol of lanthanum nitrate and dissolve it in 50 L of deionized water. Add the lanthanum nitrate solution dropwise to the humic acid solution obtained in step (1) under stirring. After dispersion for 10 min, transfer the mixed solution into a high-pressure reactor and react at 100-150° C. for 6-10 h. Rinse and dry to obtain the product.
2. The rare earth modified plastic according to claim 1, characterized in that: The rare earth modified plastic is prepared from 80% to 90% of polypropylene as a main material, 5% to 10% of a copolymer elastomer and 5% to 10% of lanthanum humate as raw materials.
3. A method for preparing rare earth modified plastics according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: weighing a polypropylene main material, a copolymer elastomer and lanthanum humate in proportion, adding the above components into a high-speed stirrer and mixing them evenly; subjecting the mixed raw materials to melt extrusion, sheet casting, biaxial stretching treatment and heat treatment in sequence to obtain a polypropylene film intermediate; and subjecting the polypropylene film intermediate to corona treatment to obtain a polypropylene film.
4. The preparation method according to claim 3, characterized in that: The biaxial stretching treatment includes a longitudinal stretching treatment and a transverse stretching treatment performed sequentially, wherein the process conditions of the longitudinal stretching treatment include: a stretching temperature of 130°C to 160°C and a longitudinal stretching ratio of 7:1 to 10:1; the process conditions of the transverse stretching treatment include: a stretching temperature of 150°C to 170°C and a stretching ratio of 3:1 to 6:
1.
5. The preparation method according to claim 3, characterized in that: The heat treatment temperature is 120° C. to 130° C., the heat treatment time is 10 to 60 seconds, the corona treatment power is 80 kW, and the line speed is 80 to 200 m / min.
Citation Information
Patent Citations
Method for improving hydrophilicity and thermal stability of polypropylene lithium-ion battery separator
CN103992505A
Raw material of high-wettability lithium ion battery diaphragm and method for processing high-wettability lithium ion battery diaphragm
CN104403195A
A preparation method of a battery composite separator
CN109148795A
Preparation method of polyolefin lithium ion battery diaphragm
CN110137416A
A silica inorganic nanoparticle-reinforced polyolefin membrane and its application
CN111725468B